2022
DOI: 10.1021/acs.jafc.2c02079
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Extracts of Coffee Cherry Husks Alleviated Colitis-Induced Neural Inflammation via NF-κB Signaling Regulation and Gut Microbiota Modification

Abstract: Coffee cherry husks, the main byproduct of coffee production, contain an abundance of polyphenols. In this study, dextran sodium sulfate (DSS)-induced colitis mice were used to study the protective effects of polyphenolic extracts of coffee cherry husks (CCHP) on inflammation. The results indicated that CCHP administration alleviated the histological changes of DSS-induced colitis in mice and downregulated the mRNA level of TNF-α, IL-1β, IL-6 and Cox-2. Interestingly, CCHP inhibited the activation of microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Polyphenolic extracts of coffee cherry husks relieved the symptoms of colitis, reduced the levels of pro-inflammatory cytokines, reduced the neutrophil infiltration and oxidative stress, and restrained TLR4/Myd88/NF-κB signaling pathway, thereby inhibiting neuroinflammation. 11 In this study, DSS induced the upregulation of p-NF-κB in the colon, while CA treatment downregulated the level of p-NF-κB. These results suggest that CA may inhibit the activation of the NF-κB pathway, thereby inhibiting the inflammatory response.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Polyphenolic extracts of coffee cherry husks relieved the symptoms of colitis, reduced the levels of pro-inflammatory cytokines, reduced the neutrophil infiltration and oxidative stress, and restrained TLR4/Myd88/NF-κB signaling pathway, thereby inhibiting neuroinflammation. 11 In this study, DSS induced the upregulation of p-NF-κB in the colon, while CA treatment downregulated the level of p-NF-κB. These results suggest that CA may inhibit the activation of the NF-κB pathway, thereby inhibiting the inflammatory response.…”
Section: Discussionsupporting
confidence: 55%
“…9 It was found that the polyphenol extract of coffee cherry peel alleviated colitis in mice by regulating the TLR4/NF-κB/MyD88 pathway and reducing inflammation. 11 Moreover, polyphenols can also enrich beneficial bacteria and inhibit the growth of pathogenic bacteria. Studies have shown that polyphenols play a protective and preventive role in colitis through a series of biochemical mechanisms mediated by gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…In colon, stomach, and liver cancer, the NF-κB and STAT3 signaling pathways work together to promote development and progression . Specifically, many polyphenols inhibit NF-κB, a key transcription factor involved in inflammation, cell growth, and survival, and play a crucial role in IBD and IBD-related colorectal cancer. The induction of cytokine expression in immune cells of the tumor microenvironment in response to NF-κB activation leads to the activation of the STAT3 signaling pathway in both malignant and immune cells . Several studies have reported increased NF-κB and STAT3 activation in IBD patients and provided evidence for the potential protective effect of plant polyphenols against colitis through NF-κB and STAT3 inhibition .…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of vitexin 91 increased the abundance of Akkermansia and reduced the abundance of Lachnospira and other bacteria, which in turn reduced reactive oxygen species levels and increased the expression and activity of antioxidant enzymes, thereby suppressing inflammatory factors and ameliorating HFD‐induced brain oxidative stress. The intake of coffee husk polyphenols 70 restored the changes in the microbiota of mice caused by DSS‐induced colitis, specifically reducing the relative abundance of Proteobacteria and increasing the relative abundance of Bacteroidetes, and thus alleviated the histological changes of DSS‐induced colitis in mice. In mice fed with an HFD, the gut microbiota was significantly reduced in genera of Muribaculaceae and Lachnospiraceae 71 .…”
Section: Diet Components Regulate Gut Microbiota‐related Diseasesmentioning
confidence: 99%